Biological activities of Murdannia species / Ashley Wasli and Nor Aziyah Bakhari - Ashley, Wasli; Bakhari, Nor Aziyah (2020)
Numerous studies have recently revealed that the genus Murdannia is well-known for its biological activities that gives them the potential use as cure for certain diseases. Biological activities of the genus Murdannia is evaluated through the contributing factor of bioactive compound that exist in the genus itself. A review and comparison study of the related literature to the biological activities of Murdannia species has been conducted in this study. The papers were gathered using online database search (Science Direct, Springer, ResearchGate, Scopus, Wiley, Taylor & Francis and others) and classified by their publication year, author, published journal, parameters, and methods. In vitro study of M. Bracteata crude extracte revealed to have anti-oxidant, cytotoxic, hepatoprotective and α-glucosidase activity. Roots extract of M. Lanuginosa has been identified to posses anti-microbial, anti-inflammatory and anti-proliferative activity. M. Simplex roots extract revealed fungicidal activity due to the presence of protamine. Crude extract of M. Nudiflora demonstrated analgesic, anti-inflmmatory, anti-oxidant, and cytotoxic activity due to the presence of major phenolic compounds. M. Loriformis possess antiinflammatory, anti-oxidant antimutagenicity, anti-ulcerogenic analgesic, DT-diaphrose and antipyretic activity which influenced by chemical constituents such as alkaloids, amino acids, flavonoids, and polyphenols that exist in the plant extract.